Inhibitory effects of Stevioside on Streptococcus mutans and Candida albicans dual-species biofilm - Guo, Mingzhu; Yang, Kuan; Zhou, Zhifei; Chen, Yujiang; Zhou, Ziye; Chen, Peng; Huang, Ruizhe; Wang, Xiaojing (Frontiers in Microbiology, 2023)
Streptococcus mutans is the most prevalent biofilm-forming pathogen in dental caries, while Candida albicans is often detected in the presence of S. mutans. We aimed to evaluate the anti-caries effect of stevioside in medium trypticase soy broth (TSB) with or without sucrose supplementation compared with the same sweetness sucrose and xylitol in a dual-species model of S. mutans and C. albicans, based on planktonic growth, crystal violet assay, acid production, biofilm structural imaging, confocal laser scanning microscopy, and RNA sequencing. Our results showed that compared with sucrose, stevioside significantly inhibited planktonic growth and acid production, changed the structure of the mixed biofilm, and reduced the viability of biofilm and the production of extracellular polysaccharides in dual-species biofilm. Through RNA-seq, Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway impact analysis showed that stevioside decreased sucrose metabolism and increased galactose and intracellular polysaccharide [IPS; glycogen, (glg)] metabolism in S. mutans, and decreased genes related to GPI-modified proteins and secreted aspartyl proteinase (SAP) family in C. albicans. In contrast to xylitol, stevioside also inhibited the transformation of fungal morphology of C. albicans, which did not form mycelia and thus had reduced pathogenicity. Stevioside revealed a superior suppression of dual-species biofilm formation compared to sucrose and a similar anti-caries effect with xylitol. However, sucrose supplementation diminished the sup-pression of stevioside on S. mutans and C. albicans. Our study is the first to confirm that stevioside has anticariogenic effects on S. mutans and C. albicans in a dual-species biofilm. As a substitute for sucrose, it may help reduce the risk of developing dental caries.